The Phonics Method to Increase English Pronunciation for Young Learners - Gumelar, Wahyu Satya; Lestari, Tyara Sucia (Jurnal Simki Pedagogia, 2024)
The purpose of this study was to solve the problem of fifth-grade students at SDN Ciwidey Kota that still low in pronunciation skills. Their English pronunciations are still considered inadequate, as seen by an average score of 52.85. This study design is Classroom Action Research (CAR). The data gathering approaches employed included an oral test, which is read aloud simple descriptive text, interviews with students and teachers, and field notes. In this study, the phonics method was employed to improve students' pronunciation skills through classroom activities. This study was carried out in two phases. The first cycle showed no significant improvements, however there was some improvement with an average score of 62.92. Cycle two was consequently required, and it showed remarkable improvement with an average score of 80.17. In short, the findings of this study suggest that the phonics method can improve students' English pronunciation skills and boost students' confidence in pronouncing a word in English. Then, during the learning process, a more effective strategy for students' pronunciation was discovered by applying the phonics method.